Asupan makan, sindrom metabolik, dan status keseimbangan asam-basa pada lansia - Nurmasari Widyastuti; Muhammad Sulchan; Andrew Johan (Jurnal Gizi Klinik Indonesia, 2013)
Background: Metabolic syndrome prevalence increases with age and obesity. The metabolic syndrome is associated with alterations in renal function. Low urine pH has been described as a renal manifestation of the metabolic syndrome. Urine pH is a simple and inexpensive method for determining acid-base status. Recent studies suggest that acid-base status is associated with dietary intake.Objective: To examine relationship between dietary intake, components of metabolic syndrome and urine pH among the elderly.Method: Subjects of this cross-sectional study consist of 49 elderly that were collected consecutively. Height, weight, waist circumference (WC), dietary intake, blood pressure (BP), fasting blood glucose and urine were obtained. Rank Spearman correlation test was used to examine the correlation of components of metabolic syndrome and dietary intake with urine pH. Mann-Whitney test was used to compare the urine pH of the metabolic syndrome group and the normal group. Chi-Square/fisher test was used to calculate prevalence ratio (PR) of metabolic syndrome components to low urine pH. Multivariate analysis was done by multiple linear regression.Results: The mean urine pH of the metabolic syndrome group was 6,06 and significantly lower than the normal group (6,50). WC was the only component of metabolic syndrome that related to urine pH (r=-0,325; p=0,023). Abdominal obesity significantly increases the risk of low urine pH (RP=1,6; p=0,023; CI=1,005-2,442). Urine pH was negatively associated with protein intake and proportion of protein on diet. In multivariate analysis, WC is the most significant factor that predicted urinary pH.Conclusion: Urine acidification is a characteristic of abdominal obesity and the metabolic syndrome. Protein intake and proportion of protein on diet contribute to urine pH.